2020
DOI: 10.1002/ijc.33151
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic events after high‐intensity training during cisplatin‐based chemotherapy for testicular cancer: Case reports and review of the literature

Abstract: The randomized "Testicular cancer and Aerobic and Strength Training trial" (TASTtrial) aimed to evaluate the effect of high-intensity interval training (HIIT) on cardiorespiratory fitness during cisplatin-based chemotherapy (CBCT) for testicular cancer (TC). Here, we report on an unexpected high number of thromboembolic (TE) events among patients randomized to the intervention arm, and on a review of the literature on TE events in TC patients undergoing CBCT. Patients aged 18 to 60 years with a diagnosis of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Overall, 8.9% of our study patients were diagnosed with an incident VTE, supporting results from two large studies [10] , [11] . In line with previous large studies [8] , [9] , [10] , [11] and a recent literature review [26] , we found that central venous access and large RPLN metastases were associated with an increased risk of incident VTE in age-adjusted analysis. Patients without any risk factors had 5% incidence of VTE, indicating a thrombotic potential of CBCT.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, 8.9% of our study patients were diagnosed with an incident VTE, supporting results from two large studies [10] , [11] . In line with previous large studies [8] , [9] , [10] , [11] and a recent literature review [26] , we found that central venous access and large RPLN metastases were associated with an increased risk of incident VTE in age-adjusted analysis. Patients without any risk factors had 5% incidence of VTE, indicating a thrombotic potential of CBCT.…”
Section: Discussionsupporting
confidence: 92%
“…In the general population and increasingly among cancer survivors, physical activity, smoking habits, and nutrition are frequently investigated components of the lifestyle's impact on overall mortality. 24,25 Admittedly, the most effective level of regular physical activity is not finally defined for cancer survivors, 42 recognizing that the highest level of training from trialbased interventions [43][44][45] rarely can be integrated into a person's regular lifetime behavior. Importantly, in childhood cancer survivors, Scott et al 25 documented the life-prolonging effect of regular physical activity comparable with $ 15 METhours per week.…”
Section: Discussionmentioning
confidence: 99%
“…Session started with 10 minutes warm‐up at 60% to 70% of heart rate peak (HRpeak), followed by HIIT; that is, 2 to 4 intervals of 2 to 4 minutes of aerobic activities performed at 85% to 95% of HRpeak, (high‐intensity zone); separated by 2 minutes of active recovery exercise, and followed by 10 minutes cool‐down. Three out of nine TGCT patients experienced thromboembolic events, possibly as a result of this strenuous exercise intervention, which clearly indicates that less intense individualized exercise interventions should be prescribed to patients during chemotherapy 32 …”
Section: Exercise In Cancer Patients/survivorsmentioning
confidence: 99%
“…Three out of nine TGCT patients experienced thromboembolic events, possibly as a result of this strenuous exercise intervention, which clearly indicates that less intense individualized exercise interventions should be prescribed to patients during chemotherapy. 32 On the other hand, it is critically important to prevent sedentary behavior that can decrease quality of life and physical well-being of cancer patients mainly because of the disease-related disruption of normal physical activity habits. Midtgaard et al 33 investigated the self-reported physical activity behavior, exercise motivation, and information regarding the education on the exercise benefits provided by the health care professional among 451 Danish adult cancer patients of 21 different diagnoses undergoing chemotherapy.…”
Section: Risks and Benefits Of Exercise Training During Chemotherapymentioning
confidence: 99%